2017
DOI: 10.1093/ajh/hpx094
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hypertension and Systolic Blood Pressure With the Risk of Stroke or Bleeding in Patients With Atrial Fibrillation: The Fushimi AF Registry

Abstract: The incidences of stroke/SE and bleeding were higher in AF and hypertension patients with elevated SBP. UMIN Clinical Trials Registry: UMIN000005834.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Data from the FUSHIMI study, which enrolled 3713 Japanese patients with NVAF, demonstrated that history of hypertension was not a predictor of ischemic stroke or major bleeding; however, uncontrolled hypertension defined as a baseline SBP ≥150 mmHg was found to be a predictor of ischemic stroke and major bleeding. 23 We also demonstrated that average SBP, which reflects sustained control of SBP, is more important than baseline SBP for predicting clinical outcome. This finding supports the theory of integrated AF management, ie the "C" of the ABC (Atrial fibrillation Better Care) pathway recommended in guidelines, which refers to cardiovascular and comorbidity risk optimization.…”
Section: Discussionmentioning
confidence: 62%
“…Data from the FUSHIMI study, which enrolled 3713 Japanese patients with NVAF, demonstrated that history of hypertension was not a predictor of ischemic stroke or major bleeding; however, uncontrolled hypertension defined as a baseline SBP ≥150 mmHg was found to be a predictor of ischemic stroke and major bleeding. 23 We also demonstrated that average SBP, which reflects sustained control of SBP, is more important than baseline SBP for predicting clinical outcome. This finding supports the theory of integrated AF management, ie the "C" of the ABC (Atrial fibrillation Better Care) pathway recommended in guidelines, which refers to cardiovascular and comorbidity risk optimization.…”
Section: Discussionmentioning
confidence: 62%
“…Hypertension is the most common risk factor for the development of AF worldwide (34). However, it remains unclear whether SBP and DBP levels are related to the risk of stroke in AF patients (35). In the present meta-analysis, the ischemic stroke group showed significantly higher BP levels and a greater risk of ischemic stroke than the nonstroke group.…”
Section: Figurementioning
confidence: 54%
“…(31) Similar results were evident for individuals presenting with a well-controlled hypertension. (32) Hypertension: There is no evidence in literature concerning the definition of hypertension as a cardiovascular risk factor. Usually the presence of hypertension is defined as the history of hypertension (including anti-hypertensive treatment at the time of assessment).…”
Section: Congestive Heart Failurementioning
confidence: 99%